Harmonizing The Distribution of Inheritance Property in Inter-Religious Families - Christofel Hutagaol, Daniel Hotma; Basani, Christin Septina (CV RIFAINSTITUT, 2024)
This study explores the harmonization of inheritance laws in interfaith families, specifically addressing the distribution of inherited assets among members with different religions. It focuses on the application and distribution of inheritance laws for interfaith families, referring to Law Number 1 of 1974 concerning Marriage and Supreme Court Circular Letter Number 2 of 2023 concerning Guidelines for Judges in Adjudicating Cases of Registration of Marriages between Believers of Different Religions and Beliefs. Applying a legal normative method, the findings conclude that there are three systems of inheritance laws in Indonesia: civil law, Islamic inheritance law, and customary law. The resolution of inheritance distribution in interfaith families within in Islam involves the application of